Gender and culture at the limit of rights - Hodgson, Dorothy Louise (Pennsylvania studies in human rights., 2011)
In this interdisciplinary, international collection of original essays, distinguished scholars, lawyers, and activists probe the complex relationship between gender, culture, and rights. The authors offer thoughtful, provocative case studies to suggest that the power of women's rights is also the source of its limits.